2020
DOI: 10.1097/mph.0000000000001826
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Needs and Experiences of Preparing for Medical Emergencies Among Children With Cancer and Their Caregivers

Abstract: BACKGROUND: Caregivers of children with cancer can experience stress when seeking care in the emergency department. We sought to assess how caregivers prepare for and manage a medical emergency that arises in the community setting. PROCEDURE:A qualitative evaluation of emergency department (ED) visit preparations taken by children with cancer and their caregivers using self-reported interactive toolkits. Eligible participants included children with cancer (age 11 -21) currently receiving therapy for a cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The research team, consisting of health communication, pharmaceutical, and medical scholars with high levels of expertise, collaborated with Research Jam, Indiana Clinical and Translational Sciences Institute's Patient Engagement Core, an interdisciplinary group of researchers with experience in patient engagement, human-centered design research, participatory design, and communication design. Research Jam assists individual investigators by engaging stakeholders in a human-centered design approach to data collection, analysis, synthesis, and solution development [ [19] , [20] ].…”
Section: Methodsmentioning
confidence: 99%
“…The research team, consisting of health communication, pharmaceutical, and medical scholars with high levels of expertise, collaborated with Research Jam, Indiana Clinical and Translational Sciences Institute's Patient Engagement Core, an interdisciplinary group of researchers with experience in patient engagement, human-centered design research, participatory design, and communication design. Research Jam assists individual investigators by engaging stakeholders in a human-centered design approach to data collection, analysis, synthesis, and solution development [ [19] , [20] ].…”
Section: Methodsmentioning
confidence: 99%
“…Poorly organized home care services caused a sense of insecurity in caregivers [ 92 ]. Long waiting times and lack of a comfortable environment during clinic visits can amplify unpleasant caregiver emotions [ 93 ].…”
Section: Factors Influencing Informal Cancer Caregivingmentioning
confidence: 99%
“…Previous research has demonstrated that approximately half of the children with cancer will seek emergency department (ED) care within the first year after diagnosis [ 13 ]. Through our explorations of the experience of children with cancer and their caregivers when medical emergencies arose in the community setting, we found that the key components for emergency preparedness included the ability to easily connect with the oncology team, having a packing checklist, and an informational card to show the ED staff [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%